Baseline parameters for rotational thromboelastometry in healthy labouring women: a prospective observational study. (11th February 2020) - Lee, J; Eley, VA; Wyssusek, KH; Kimble, RMN; Way, M; Coonan, E; Cohen, J; Rowell, J; van Zundert, AA
Abstract : Objective: The aim of this study was to establish rotational thromboelastometry (ROTEM ® ) baseline parameters in labouring women at term gestation. The secondary aim was to compare these reference ranges with those from previous studies on labouring women and from the manufacturer. Design: A prospective, observational study. Setting: Tertiary referral hospital. Participants: Healthy women in labour. Methods: Ethics approval was granted for an opt‐out recruitment approach. ROTEM ® testing was performed in labouring women at term gestation. Women with any condition affecting coagulation were excluded. ROTEM ® Delta reference ranges were derived by calculating the 2.5% and 97.5% centiles for INTEM/EXTEM/FIBTEM parameters including amplitude at 5 minutes (A5), coagulation time (CT) and maximum clot firmness (MCF). Main outcome measures: ROTEM ® parameters were measured in labouring women before delivery. The following tests were performed: FIBTEM, EXTEM and INTEM. Results: One hundred and twenty‐one women met the inclusion criteria, with a mean (± SD) age of 29.6 ± 5.4 years and median (interquartile range) gestation of 39.4 weeks (37.4–40.4 weeks). Seventy‐five (62.0%) women were nulliparous and 71 (58.7%) delivered vaginally. The median and interquartile ranges for selected ROTEM ® parameters were: FIBTEM A5, 21 mm (IQR 18–23 mm); EXTEM A5, 55 mm (52–58 mm); and EXTEM CT, 52 seconds (48–56 seconds). Conclusions: The FIBTEM/EXTEM/INTEM amplitudes were higher than the manufacturer's reference ranges for non‐obstetric patients. The FIBTEM MCF upper and lower limits were higher and the EXTEM/INTEM CT was shorter and narrower in range. This study provides reference ranges for ROTEM ® values in healthy labouring women at term gestation with uncomplicated pregnancies. Tweetable abstract: This is the first study to report on ROTEM ® reference ranges with over 120 healthy labouring women of normal weight at term gestation. Tweetable abstract: This is the first study to report on ROTEM ® reference ranges with over 120 healthy labouring women of normal weight at term gestation.